براعة الزّمخشري في وعظ المسلمين من خلال مقاماته: من منظور علم النّص: علم النّصّ، اتّساق النّص وانسجامه، الزمخشري، مقامات الزّمخشري، البلاغة العربية - Ù…ØÙ…Ø¯ Ø¹ØµÙ…Øª, Ù†ÙˆØ± Ø§Ù„ØÙ†ÙŠÙ„Ø©; Ø¹Ø¨Ø¯ Ø§Ù„Ø¹Ø²ÙŠØ², Ø¹Ø¨Ø¯ Ø§Ù„Ù‡Ø§Ø¯ÙŠ (Al-Ḍād Journal, 2018)
This study aims to explore the elements of cohesion and coherence in analysing Zamakhshari’s Maqāmāt. The study also made use of traditional Arabic linguistic heritage – al-Balāghah al-‘Arabiyyah - in its text analysis and its relevancy with western textual perspective in the framework of Zamakhsari’s Maqāmat. The study concluded that Zamakhshari utilized cohesive devices such as continuity, reference, repetition, inclusion, substitution; he also used figurative tools in his Maqāmāt such as allegories, metaphors and imageries to persuade and influence readers. Therefore, the application of textuality is excellently applied by Zamakhshari in his works.